The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3122/jabfm.2015.06.150080
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Parents Caring for Infants with Rare Scalp Mass as Identified through a Disease-Specific Blog

Abstract: Background: Delayed subaponeurotic fluid collection (DSFC) is a self-limited disorder of unknown etiology characterized by a benign, fluid-filled mass in the subaponeurotic layer of an infant's scalp. While a few case series describe DSFC, the experiences of families whose infants develop this condition have not previously been reported.Methods: We used a disease-specific blog to evaluate the experiences of 69 families affected by DSFC. We identified self-reported clinical features of DSFC and qualitatively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Some of the themes that emerged from the research included lack of provider awareness, concern about unnecessary diagnostic procedures, and parental anxiety regarding accusations of child abuse. 15 Hopefully, as increased physician awareness regarding this rare entity emerges, there will be improved understanding of the benign and self-resolving nature of SSFC, and a reduction in unnecessary diagnostic testing, child abuse investigations, inpatient admissions, and interventions.…”
Section: Table 2 Summary Of 21 Previously Reported Pediatric Cases Omentioning
confidence: 99%
“…Some of the themes that emerged from the research included lack of provider awareness, concern about unnecessary diagnostic procedures, and parental anxiety regarding accusations of child abuse. 15 Hopefully, as increased physician awareness regarding this rare entity emerges, there will be improved understanding of the benign and self-resolving nature of SSFC, and a reduction in unnecessary diagnostic testing, child abuse investigations, inpatient admissions, and interventions.…”
Section: Table 2 Summary Of 21 Previously Reported Pediatric Cases Omentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Since its rarity and limited cases reported around the world, many physicians never seen DSFCs before and may not recognize its clinical entity in the first place; Worthen et al published article concerning rare scalp mass that identified through a disease-specific blog, analyzing experiences of 69 families whose infants developed DSFCs. [17] Hopkins et al reported the first six cases of DSFCs that managed conservatively and one case was managed by a needle aspiration of the collection on two occasions when serosanguinous fluid was aspirated ×2 after diagnosis. [3] Schoberer et al [11] and Munjal and Kumar [8] reported one case managed by 2 times aspiration, since they observed the reaccumulation of the fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-five percent of infants were evaluated in a primary care setting and 38% in the ED. 1 All participants reported that providers were unaware of the clinical features of SFC, which led to imaging in 100% of cases and included exposure to radiation (53% cases), repeated evaluation, and in some cases referral to specialists and/or suspicion of child abuse (9 cases). 1 Many responders felt medical evaluation increased rather than relieved their concerns.…”
Section: Discussionmentioning
confidence: 99%